Intertemporal Social Efficiency on Indonesian Islamic Banks: DEA Window Analysis - Aam Slamet Rusydiana; Mohammad Iqbal Irfany (SMART Insight, 2023)
Measurement of the efficiency level of Islamic banks in Indonesia is widely carried out, but almost no study has been conducted with the DEA window analysis approach, especially in the 'social efficiency' perspective. We try to measure the social efficiency of the Islamic banks in Indonesia employing both Data Envelopment Analysis (DEA) and the DEA window analysis. For certain cases the results of the DEA window analysis are relatively more stable and can illustrate the actual results of the efficiency value. The results show that the social efficiency of Islamic banks in Indonesia from 2011-2018 are relatively fluctuated but tend to increase. From the perspective of the stability of efficiency value, we found only 4 (four) out of 11 (eleven) Islamic banks that have relatively stable efficiency levels.